Effect of aortic arch type on technical indicators in patients undergoing carotid artery stenting. Issue 2 (February 2019) - Shen, Songhe; Jiang, Xiongjing; Dong, Hui; Peng, Meng; Wang, Zhixue; Che, Wuqiang; Zou, Yubao; Yang, Yuejin
Objective: This study was performed to explore the effect of the aortic arch type on technical indicators in patients undergoing carotid artery stenting (CAS). Methods: The data of 224 consecutive patients who underwent unilateral CAS from January 2011 to December 2012 were retrospectively analyzed. The requirement for placement of the guiding catheter into the common carotid artery with assistance of an angiographic catheter, fluoroscopy time, contrast agent dose, and adverse events were recorded. Results: The fluoroscopy time was significantly longer and the contrast agent dose was significantly higher in patients with Type III than Type I and II arches. Significantly more patients with Type III than Type I and II arches required placement of the guiding catheter with assistance of an angiographic catheter (46.2% vs. 15.0%, respectively). The procedural success rate was significantly lower in patients with Type III than Type I and II arches (96.2% vs. 100.0%, respectively). The incidence of death, myocardial infarction, and all types of stroke was significantly higher in patients with Type III than Type I and II arches (7.7% vs. 1.7%, respectively). Conclusions: The aortic arch type is an important influential factor in CAS. Type III arches are associated with more difficulties and complications.